A report on the contribution of the Inter-American Institute for Cooperation on Agriculture to the agricultural sector of Jamaica during 2000 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
50 páginas